Enforcement of antenuptial contracts - Malaza, Siyabonga Meshack (https://orcid.org/0009-0003-4132-2903) (Rhodes University, 2026)
Embargo applied. Embargo period to expire in March of 2028.
striking a balance in the protection of spouses
Keywords: Prenuptial agreements (http://id.loc.gov/authorities/subjects/sh85005513); Law